Structural behavior of the old masonry bridge in the Gulf of Castellammare. (April 2016) - Bergamo, O.; Campione, G.; Cucchiara, C.; Russo, G.
Abstract: Masonry arch bridges represent a very significant part of the heritage of road and railway artworks all over the word and especially in the Mediterranean area, both in terms of: numbers; reduced environmental impact; and static efficiency. In these cases, the cost of maintenance is often limited to the content and channeling of surface water and control of vegetation, which can eventually take root on the joints of the masonry at the shoulders. In masonry bridges, there are no expansion joints or hinges with support equipment or trolleys, as in metal bridges and reinforced concrete ones, or paint, or resin surface protection, all items that affect the cost of maintenance. The permanent weight of these bridges is very high and, together with the mechanical characteristics of the structure, results in very high strength and stiffness against moving loads. This is one of the most valuable aspects of masonry arch bridges, making it possible to keep open to traffic safely, without repair actions, bridges that are centuries old and which are now subject to vehicular traffic and trains producing actions that are considerably higher than those for which they were originally designed. The purpose of this work was a static check on the old Gate Bridge, a road bridge in masonry which links Corso Garibaldi and Via Giacomo Puccini in the town of Castellammare del Golfo (Trapani province). An extensive experimental research was carried out for in situ mechanical characterization of the constituent materials and static tests were also carried out to study the structural response (load–deflection curves) of the arch bridge. Finally, analytical and numerical analyses were carried out for safety verification of the arch stone and for verification of the serviceability condition. Highlights: Old existing road masonry bridge Extensive experimental research with in situ mechanical characterization of the constituent materials Static tests for studying the structural response of the arch bridge Numerical analyses were carried out for safety verification of the arch stone.